2010
DOI: 10.1038/cmi.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide alleviates airway hyperresponsiveness and eosinophilia in a murine model of asthma

Abstract: Asthma is one of the most common chronic airway inflammatory diseases. The clinical hallmarks of asthma include elevated serum levels of immunoglobulin E (IgE), eosinophilic inflammation and airway hyper-responsiveness (AHR). Arsenic trioxide (As 2 O 3 ) is considered a carcinogen; however, it has also been used to treat diseases, such as syphilis, in traditional Chinese and Western medicine. Today, As 2 O 3 is used as one of the standard therapies for acute promyelocytic leukemia (APL). Previous studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Thirdly, the therapeutic use of arsenic in the formulation known as "Fowler's solution", first recognized in the London Pharmacopoeia of 1890, was well-known for treating severe asthma as indicated in the 11th edition (in 1989) Merck index [14,33]. Interestingly, recent animal models have also suggested a therapeutic role of arsenic trioxide in alleviating airway hyperresponsiveness and eosinophilia [34,35]. Therefore, the short-term therapeutic use of arsenic trioxide as in our cohort may even potentially improve the pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the therapeutic use of arsenic in the formulation known as "Fowler's solution", first recognized in the London Pharmacopoeia of 1890, was well-known for treating severe asthma as indicated in the 11th edition (in 1989) Merck index [14,33]. Interestingly, recent animal models have also suggested a therapeutic role of arsenic trioxide in alleviating airway hyperresponsiveness and eosinophilia [34,35]. Therefore, the short-term therapeutic use of arsenic trioxide as in our cohort may even potentially improve the pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…For basophils, the direct effects of As(III) have not yet been investigated. However, activation of basophils may be impaired in vivo during As(III) administration, because levels of IgE, an important driver of basophil activation, were decreased in the BALF of As 2 O 3‐ treated mice (Chu et al, 2010; Zhou et al, 2006). For mast cells, it was reported that NaAsO 2 inhibits anti‐IgE stimulated degranulation via suppression of early tyrosine phosphorylation (Hutchinson et al, 2011).…”
Section: The Multifaceted Effects Of Trivalent Arsenic On Immune Cellsmentioning
confidence: 99%
“…In addition, it has been demonstrated that arsenite influences various cellular processes like apoptosis, proliferation, inflammation, angiogenesis, and immune response . Therapeutically, arsenic compounds have often been used in traditional Chinese and Western medicine for decades to treat several diseases including tooth diseases, rheumatosis, psoriasis, syphilis, and trypanosomiasis . Arsenic compounds have shown remarkable potency against acute promyelocytic leukemia and have become one of the standard therapies for acute promyelocytic leukemia .…”
Section: Introductionmentioning
confidence: 99%